2001
DOI: 10.1209/epl/i2001-00179-4
|View full text |Cite
|
Sign up to set email alerts
|

Fragile vs . strong liquids: A saddles-ruled scenario

Abstract: PACS. 61.20.Gy -Theory and models of liquid structure. PACS. 64.70.Pf -Glass transitions.Abstract. -In the context of the energy landscape description of supercooled liquids, we propose an explanation for the different behaviour of fragile and strong liquids. Above Goldstein's temperature Tx, diffusion is interpreted as a motion in the phase space among saddles of the potential energy. Two mechanisms of diffusion then arise: mechanism A takes place when the system overcomes potential energy barriers along stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 24 publications
6
76
0
Order By: Relevance
“…The physical interpretation of this transition is rather simple: above the phase transition the system is near a saddle point of the Hamiltonian, whereas below it the system is near a local minimum of the Hamiltonian (63)(64)(65)(66)(67). This picture is very interesting, also because it gives a clear explanation of the origin and of the properties of the celebrated boson peak (68).…”
Section: Structural Fragile Glassesmentioning
confidence: 98%
“…The physical interpretation of this transition is rather simple: above the phase transition the system is near a saddle point of the Hamiltonian, whereas below it the system is near a local minimum of the Hamiltonian (63)(64)(65)(66)(67). This picture is very interesting, also because it gives a clear explanation of the origin and of the properties of the celebrated boson peak (68).…”
Section: Structural Fragile Glassesmentioning
confidence: 98%
“…[30], in analogy with what happens in mean field models [31,32]: the vanishing as T approaches T c of the mean intensive number of negative directions (intensive index) of stationary points of the potential energy, n s (T ). Numerical simulations [33,34,35,36,37,38] found that n s (T ) decreases with decreasing T , and fits were performed to show that n s (T c ) = 0 [33,34,35].…”
Section: Introductionmentioning
confidence: 94%
“…17,18,19,20,21,22,23 High-order stationary points could offer a simple explanation of the fragile behavior of glass-formers, in terms of an increase of average energy barriers. 24 This feature is encoded, in an effective way, in a number of models of energy landscapes developed in the last years, 25,26,27,28 and has sometimes been addressed in numerical simulations. 29 Statistical properties of high-order stationary points of the PES have been investigated recently for a variety of monoatomic and binary systems, both in the liquid 30,31 and supercooled regime.…”
Section: Introductionmentioning
confidence: 99%